“Mãe perdoa assassino do filho” : ressentimento social e espetacularização do perdão na cena midiática brasileira - Ananias, Fernando Ferreira da Silva (2022)
In this dissertation, I sought to describe and analyze, through a discursive perspective, the spectacularization of forgiveness in the Brazilian Media Scene, focusing on reports starring mothers who claim to forgive their children’s killers. Therefore, the corpus was composed of three police newscasts’ editions (Brasil Urgente, Caso de Polícia and Band Cidade), an edition of Globo Repórter (2013), and also including, as parallel material to the thematic focus of the corpus, the ad campaign of the telenovela Amor de Mãe (2019) – in order to subsidize the analysis regarding the discursive construction of the motherhood imaginary in circulation. Affiliated to Discourse Analysis, through Maingueneau's perspective, this research is based upon the notions of Discursive Ethos (MAINGUENEAU, 2020) and Enunciation Scene (MAINGUENEAU, 2008). As an interdisciplinary theoretical contribution, this work is built upon Maria Rita Kehl's (2020) reflections on Social Resentment (mainly the camouflaged resentment in Brazilian society), Marilena Chauí's (1998; 2000) studies on the formation of the Brazilian nation (especially the myth of Brazilian non-violence), and Hollanda's considerations, through the concept of the Cordial Man (2012), regarding the national character. Paying attention, mainly, to the way the mother-who-forgives-the-slaughter-of-the-child event was addressed by the media segments selected in our analysis, It was possible to elaborate the following discussions: i) the representation of mothers as beings who are allegedly born (speaking in a divine level) to forgive; ii) as an extension of the first question, the representation of maternal love as an unconditional love, above all else; iii) the Brazilian "vocation" for happiness; iv) and the qualification of forgiveness as a moral distinctive and prerogative for health and well-being. Guided by Discourse Analysis and the contributions of psychoanalysis, philosophy and sociology, the analysis was led, above all, to the understanding of the discursive functioning of social resentment in the constitution of the merciful maternal ethos – imbricated to an ethos of Brazilianness – that emerges in the Brazilian Media Scene.